Measurement of Potential Tourism Destination: A Case Study - Popy Rufaidah (Jurnal Bisnis Manajemen, 2016)
This study was aimed to discuss study result to measure destination potentials in West Java, Indonesia that was conducted empirically. Based on the literature, there is still no clarity in technic and how to measure tourism destination potentials. Therefore, this paper has an advantage as a paper that discusses the measurement of tourism destination potentials with quantitative approach. The research method employed for the research reported in this paper was the case study research method. The research completion reported in this paper took place over a nine month period (from April to December), and involved field surveys to measure and analyse potential destination tourism object and their development. Potential tourism destination is the attractiveness contained in an area to be developed as untapped or not managed well to become a qualified attraction and able to attract tourists to come to the area. The formula proposed by Beciu and Hontus (2014) was adopted in this study to measure the potential of tourism destinations, namely, (1) Index of Global Tourist Demand Change, (2) Index of Domestic and Foreign Demand Variation in Time; (3) Indicator of Total Accomodation Capacity Evolution; and (4) Index of Global Tourist Demand Distribution. The study conclude that the priority for West Java Province to develop the tourism destination are, firstly, SubangRegency, secondly, Sukabumi Regency and lastly, Depok City. The recommendation of the study is proposed that in measuring thepotentialtourism destination, itis very important foreverygovernment to consider the ranking of each regencies / cities based on above mentoned index. In particular,the governmentrequiresa rankingforeacharea (regencies and or cities) in allocating the budget.